The Role of Islamic Religious Education Teachers in Increasing Students' Spiritual Intelligence at Madrasah Ibtidaiyah Negeri 2 Boyolali - Tri Wahyuningsih; Meti Fatimah (Didaktika: Jurnal Kependidikan, 2024)
The aim of this research is to find out in depth the role of Islamic religious education teachers in improving spiritual intelligence at MIN 2 Boyolali. This research uses a qualitative approach with descriptive methods. Research The subjects of this research was teachers and students of Madrasah Ibtidaiyah Negeri 2 Boyolali with informants in this research being the principal, PAI teachers, curriculum sie, student affairs sie, spiritual sie and students. Data collection was carried out through interviews, observation and documentation. Data analysis uses data reduction, presentation and conclusion drawing techniques. Checking the validity of the data was carried out using triangulation and using various theoretical sources and methods. The results of this research show that the teacher's role in increasing students' spiritual intelligence at MIN 2 Boyolali is as a teacher, educator, motivator and model. Meanwhile, the implementation strategy for increasing students' spiritual intelligence at MIN 2 Boyolali is carried out through religious activities which are carried out routinely every day and through learning in the classroom. The religious activities in question are reciting the Koran together, dhuha prayers in congregation, reading Asmaul Husna, morning inspirational stories, learning recitations, memorizing selected verses, fardhu prayers in congregation, and fasting on Mondays and Thursdays.